Corporate communication, public relations, and mobility in communication crisis handling in the insurance industry - Constantin, Natasha; Irwansyah, Irwansyah (Universitas Wiralodra, 2024)
Currently, a communication crisis continues to be seen as a frightening menace that may disrupt the seamless operation of many activities in social life, business, and organizations. Instances of communication crises have perennially occurred within enterprises and organizations. This phenomenon is not limited to external communication with audiences outside the corporation or organization but may also manifest inside and within the organization itself. Effective communication is crucial in successfully navigating through the crisis. The coordination of crisis management within an organization or corporation is handled mainly by the Corporate Communication CC and Public Relations/PR departments. Corporate communication and public relations officers must be able to analyze the causes and repercussions of crises, formulate plans to resolve them, and enhance the organization's image. These skills are essential in coordinating with other departments. The study aims to assess and investigate crisis management processes from a Corporate Communication and Public Relations viewpoint. It focuses on the digital era, where efficient crisis-handling protocols are necessary due to the need for high mobility and the use of technology. This study is grounded on a qualitative methodology that utilizes phenomenological approaches. The decision to use phenomenology was based on the informants' experiences prioritizing objectives, namely the functionaries in the two departments, to better understand the challenges encountered. The final results demonstrate that the crisis management process begins when a possible crisis is identified, including methods for preventative measures and preparedness in the event of a crisis.